2016
DOI: 10.3174/ajnr.a4891
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Patients Demonstrate Progressive T1-Weighted Hyperintensity in the Dentate Nucleus following Multiple Doses of Gadolinium-Based Contrast Agent

Abstract: Background and Purpose While there have been recent reports of brain retention of gadolinium following gadolinium-based contrast agent (GBCA) administration in adults, a retrospective series of pediatric patients has not previously been reported. We investigated the relationship between the number of prior GBCA doses and increasing T1 signal in the dentate nucleus on unenhanced T1-weighted MR imaging. We hypothesized that, despite differences in pediatric physiology and the smaller GBCA doses pediatric patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 31 publications
7
56
0
Order By: Relevance
“…(GBCAs). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Many of these reports have focused on apparent differences between macrocyclic and open-chain "linear" GBCAs, [4][5][6][7][8][9][10][11][12][13] invariably associating progressive T1 hyperintensity with multiple exposures to linear GBCAs and concluding that observed T1 signal reflects the lower stability of these agents and thus a greater propensity for gadolinium (Gd) release and, subsequently, deposition in the brain. Among the more recent reports are several that describe retrospective assessments in pediatric patients.…”
mentioning
confidence: 99%
“…(GBCAs). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Many of these reports have focused on apparent differences between macrocyclic and open-chain "linear" GBCAs, [4][5][6][7][8][9][10][11][12][13] invariably associating progressive T1 hyperintensity with multiple exposures to linear GBCAs and concluding that observed T1 signal reflects the lower stability of these agents and thus a greater propensity for gadolinium (Gd) release and, subsequently, deposition in the brain. Among the more recent reports are several that describe retrospective assessments in pediatric patients.…”
mentioning
confidence: 99%
“…Two recent developments have generated interest in decreasing the use of intravenous gadolinium‐based contrast materials. The first was the concern that has arisen regarding gadolinium deposition within and outside of the brain and potentially related toxicity in children undergoing multiple surveillance MRI examinations utilizing gadolinium . Brain and bone tissue deposition of gadolinium has been detected even in patients with normal renal function, although the clinical consequences (if any) are currently unclear .…”
mentioning
confidence: 99%
“…The first was the concern that has arisen regarding gadolinium deposition within and outside of the brain and potentially related toxicity in children undergoing multiple surveillance MRI examinations utilizing gadolinium. 8 Brain and bone tissue deposition of gadolinium has been detected even in patients with normal renal function, although the clinical consequences (if any) are currently unclear. 9 Therefore, at our institution, we In the attempt to minimize gadolinium exposure and to increase the sensitivity to detect nonenhancing leptomeningeal spinal disease, newer noncontrast MRI techniques have been suggested.…”
mentioning
confidence: 99%
“…1 [15][16][17][18][19], showed a significant decrease in the time spent on the rotarod on day 3 in both GBCA-treated groups (gadoterate meglumine-treated group, p < 0.001 and gadodiamide-treated group, p < 0.001, by ANOVA followed by Bonferroni test) compared with that in the control group. ***p < 0.001…”
mentioning
confidence: 99%
“…After (a) repeated reports of signal intensity (SI) increase in the dentate nuclei and basal ganglia on brain T1-weighted images of pediatric patients who underwent several contrastenhanced MRI scans with administration of linear products [16][17][18][19] and (b) a study with no SI after gadobenate administration [20], an autoptic study of three children has confirmed the deposition of gadolinium in the dentate nucleus, globus pallidus, and at a smaller concentration in the thalamus and pons, after more than 3 administrations of gadodiamide, a linear GBCA [21]. Pathological changes were also observed in the dentate nuclei (gliosis, axonal spheroids).…”
mentioning
confidence: 99%